Sharp Response Microstrip LPF using Folded Stepped Impedance Open Stubs - Makki, Seyed Vahab Al-Din; Ahmadi, Arash; Majidifar, Sohrab; Sariri, Hossein; Rahmani, Zeynab (Společnost pro radioelektronické inženýrství, 2013)
A novel microstrip lowpass filter with high selectivity and wide stopband is proposed that comprises two lateral folded open stubs and a central mirrored semi-circle ended suppressing cell. The proposed filter has cut-off frequency of 2.28 GHz and is very compact. The stopband width with attenuation level more than -20 dB is equal to 5.47 fc and the transition band is only 0.14 GHz. This filter is designed, fabricated and measured and the simulated and measured results are in good agreement
Keywords: Low pass filter; microstrip technology; folded open stub; sharp response; wide stopband